Secteur TIC et refonte de la gouvernance urbaine - Divya Leducq (Netcom)
There are two main reasons explaining the appearance of immature local governance organizations in India: one is the economic globalization (increasing Indian share in the international trade) and the other is linked with the political reforms (decentralization for instance). The aim of this article is to scrutinize the recasting of governance in Pune, a major city located within the south-western state of Maharashtra. At the same time ground and effect of the enlarging knowledge economy, the business associations institute strategies in order to advantage the “Queen of Deccan” in a globalized ICT services system. So, the growing influence of those private and corporate lobbies fully revamps the urban area and allocates player’s new roles on the urban administration stage. Indeed, the technopolitan space achievement goes to the expense of a sustainable urban development.